If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -3m = -17 Solving 1 + -3m = -17 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3m = -17 + -1 Combine like terms: 1 + -1 = 0 0 + -3m = -17 + -1 -3m = -17 + -1 Combine like terms: -17 + -1 = -18 -3m = -18 Divide each side by '-3'. m = 6 Simplifying m = 6
| 5q+4=8q-5 | | 4k^2+8k=0 | | -8d-5d+7d=71 | | 18+b=x | | 5x21/2 | | -r-4=-2 | | 2a-(5/a-1)=0 | | 99n+4=40 | | 5x-13=38 | | 3u-3=3u-6 | | 0=p+19 | | x-35=0 | | F(k+2)=3(2)+7 | | 21/26y=7 | | 23=23+x | | 0=4x^2+79x+376 | | y=1.3(-8)-8 | | -23=8(u+2)+5u | | 9x-3(x+5)=5x+9-3x | | x/10+1/3=x/5+1/2 | | -p=7/4 | | 4r-2=-6 | | 3y+2x=180 | | y=1.3(-8)(-8) | | 3x+7=180 | | x-1=3x-2 | | 29=7(y-7)+6y | | w/-3+14=5 | | 1/7h=300 | | -3y=14.7 | | 6/7y=2/3 | | (2+x)(3+x)-16=x |